TREND OF SMOKING AMONG STUDENTS AND EFFECTS OF SMOKING ON SOCIETY - Shahzad, Naeem; Naz, Tabssum; Usmani, Feroz; Khan, Zunaira; Rana, Naureen; Zahra, Rida; Khuram, Hafiza Rukhsana (The journal of contemporary issues in business and government, 2021)
Smoking is very dangerous problems all over the world. Smoking is dangerous not only for light smokers, but also for others. Smoking is considered one of the 10 leading factors contributing to health problems worldwide, and is considered harmful substance that causes multiple organ dysfunctions and death. This research examines the attitude of students towards cigarettes use, what they like about smoking, their knowledge regarding their health, what they dislike about smoking, parents control regarding smoking, their thoughts regarding giving up smoking, their future perspective about health and also aim of the study is to create health awareness among the people. ANOVA Model was used in statistical data fit and Suitable. The ANOVA model is acceptable and significant at the level of 1%.